Manajemen Stres dengan Latihan Mindfulness pada Mahasiswa di Masa Pandemi Covid-19: Students’ Stress Management through Mindfulness Training during Covid-19 Pandemic - Maria Komariah; Kusman Ibrahim; Tuti Pahria (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2022)
College students are a vulnerable group to go through general mental disorders, such as stress due to the influence of the social environment, pressure from parents and friends, or a competitive atmosphere. Stress harms physical and psychological, reducing academic ability and achievement index until it appears of negative behavior. Mindfulness therapy is one of the non-pharmacological therapies to reduce stress levels through awareness of current experiences by accepting without judging anything so that new perspectives come up in looking at problems and alternative solutions. This study examines mindfulness interventions' role in optimizing student stress management. The research subjects were 51 students. Measuring instruments pre-test and post-test gave before and after the intervention used Depression Anxiety Stress Scales (DASS-42). The intervention was carried out face to face through the Zoom Meeting media. The results showed that students' stress levels decreased after mindfulness training. Therefore, students practicing mindfulness in the long term can help maintain mental health stability and prevent stress.